The Value of Islamic Education in the Mappatamma' Tradition (Khatam Al-Qur’an) in the Bugis-Makassar Community - Jumadi; Walid, Abdul; Baduka, Masykur; Djollong, Andi Fitriani (CV. Eureka Murakabi Abadi, 2024)
The Mappatamma' (Khatam Al-Qur'an) tradition for prospective brides in the Makassar tribal community, when they want to get married, is a momentum that must be carried out from their perspective. This study aims to describe the implementation procedures and reveal the value of Islamic education in the Mappatamma' tradition in the Bugis-Makassar Tribe. The approach used in this study is phenomenology. This study used qualitative methods to describe the procedures for implementing and describing the value of Islamic education in the Mappatamma tradition. Data collection methods through observation, interviews, and documentation were then analyzed using triangulation. The results of the study show that the Mappatamma tradition is an interesting tradition full of values because this tradition is not only a means of traditional entertainment in cultural globalization, but the tradition is full of meanings and messages that express the value system adopted by the community. The Makassar tribe contains many values ​​of Islamic education, namely faith, morals, intellectual, physical and psychological, and social education.